2014
DOI: 10.1007/s12039-013-0549-9
|View full text |Cite
|
Sign up to set email alerts
|

Separation and isolation of tautomers of 2-hydroxy-4-naphthoquinone-1-oxime derivatives by liquid chromatography: Antiproliferative activity and DFT studies

Abstract: Reversed phase HPLC separation and isolation of isomers of 2-hydroxy-4-naphthoquinone-1oxime (Lwox) and 3-methyl-2-hydroxy-4-naphthoquinone-1-oxime (Phox) have been investigated. Two distinct peaks are observed in the chromatogram of Lwox and are assigned to 'para' tautomer; 2-hydroxy-4naphthoquinone-1-oxime (3) and 'ortho' tautomer; 4-hydroxy-2-naphthoquinone-1-oxime (4). The tautomeric equilibrium of 3 and 4 has been manipulated by incrementally increasing the pH of the mobile phase from 2.5 to 10.5, and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The retention time of peak-1 is 8.3 min and peak-2 is 9.1 min with peak area 1.47% and 98.53% respectively. Although the peak area is negligible the nature of chromatogram is similar to what is observed for tautomers 13 . Based on the peak areas it can be concluded that the tautomer stability at peak II is maximum.…”
Section: Separation Of Tautomers Of O-hydroxyanilino-14-naphthoquinosupporting
confidence: 66%
See 4 more Smart Citations
“…The retention time of peak-1 is 8.3 min and peak-2 is 9.1 min with peak area 1.47% and 98.53% respectively. Although the peak area is negligible the nature of chromatogram is similar to what is observed for tautomers 13 . Based on the peak areas it can be concluded that the tautomer stability at peak II is maximum.…”
Section: Separation Of Tautomers Of O-hydroxyanilino-14-naphthoquinosupporting
confidence: 66%
“…The tautomers of o-hydroxyanilino-1,4-naphthoquinone derivatives have been investigated in this report with the help of 1 H, 13 C, DEPT, gDQCOSY, gHSQCAD NMR experiments, HPLC and cyclic voltammetry. All the compounds exists as 'ortho'and 'para' tautomers in DMSO-d 6 solvent and only 'para' tautomer is predominant in CD 3 CN solvent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations